Fabrication of a nano-scale pattern with various functional materials using electrohydrodynamic lithography and functionalization. Issue 7 (13th January 2016) - Lee, Suok; Jung, Sang Hee; Kang, Dae Joon; Lee, JaeJong
Abstract : Direct patterning with inorganic based materials has been developed using electrohydrodynamic lithography. Various sizes and morphologies of inorganic patterns were successfully replicated. Abstract : Direct patterning with inorganic based materials has been studied using many lithographic techniques. Among lithographic methods, electro-hydrodynamic lithography (EHL) is a good candidate to obtain a fine inorganic pattern. Being a minimal contact patterning technique, our method is simple, versatile and inexpensive, and has the potential to become a powerful tool for realizing inorganic based nanostructures on a wafer scale. Inorganic precursor resists are exploited here as relatively high-speed resists compared to macromolecule resists in an effort to reduce the patterning time significantly. These resists are developed to have functionalities via a thermal annealing process which can be used in versatile applications. An amorphous inorganic precursor pattern fabricated by EHL is transitioned to a crystalline phase via an annealing process. Herein, functional material patterns such as TiO2, VO2, Fe3 O4, and PZT are successfully fabricated and functionalized via EHL and the annealing process.